What are Impressive Aswaja's Educational and Literacy Strategies to Prevent Radicalism in Indonesia? - Abdullah, Muhammad Yahya; Kaderin, Ridwan (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
Ahlu Sunnah wal Jamaah (abbreviated by Aswaja) is one of the Islamic Aqidah adherents in Indonesia. Aswaja has played an important role in the unity and integrity of the Indonesian nation since time immemorial. This role continues in the modern era in maintaining the integrity of the nation from civil divisions, one of which is caused by radicalism in a pluralistic society. In this research, it will be known how Aswaja Islam's strategies are in protecting the integrity of the Indonesian nation from radicalism issues through the fields of education and literacy. The research method used in this qualitative research is a systematic literature review, which aims to synthesize several previous articles in the 2019-2023 period related to Aswaja Islamic education and literacy strategies in countering radicalism. The results of this research construct five literacy strategies and twelve educational strategies that have been applied by Aswaja Islam as a preventive measure against radicalism in Indonesia in this modern era. Through this finding, it can inform policy makers to design and implement educational curricula that incorporate Aswaja’s strategies for countering radicalism, fostering a more inclusive and tolerant environment in schools and universities. Furthermore, The government also can develop literacy programs that emphasize critical thinking, understanding of Aswaja principles, and the importance of national unity to prevent radicalism.